La Calidad De Atención Y Su Relación Con La Gestión Estratégica “Centro De Salud Enrique Ponce Luque” Ciudad De Babahoyo, Provincia Los Ríos. - Mestanza Segura, Cesibel (2014)
This research work, we do it based on the need to improve the quality of care in Luque Center Enrique Ponce, applying the fundamentals of strategic management as at the present time by the saturation of services, they have collapsed. Be relevant to all health units implement this type of tool. Quality assurance is the provision gear and proper use of human planned activities of economic resources, materials and process documentation, in short everything necessary for the tasks and operations are developed in ensuring quality outcomes elements minimized to the maximum sources of error. We can add to construct a system of quality improvement involves a set of systematic, continuous and deliberate actions aimed at avoiding, preventing or promptly resolve situations that may adversely affect obtaining the greatest possible benefit for patients with lower risks . These actions relate to the design of the health system, the management is carried out for this design to meet its objectives, the information collected to monitor their performance and the actions taken to correct deficiencies. The idea is to raise the standard of care, regardless of how good it is now, by a search for continuous improvement. In the present proposal are two important aspects, these being:  Develop a management model for UO administration, applying the principles of strategic management.